Design And Performance Analysis Of A Small Two-Stroke Direct Injection Diesel Engine. - Loh, Jian Haur (2011)

(untitled)
As oil resources are rapidly being depleted, vehicle fuel efficiency is becoming more important for consumers. Due to the large number of motorcycles, improving fuel consumption of motorcycles would greatly reduce fuel demand in many developing countries. Diesel engines offer the advantages of improved thermal efficiency, lower pumping losses, lean operation and potentially low friction from low speed operation with the major disadvantages being a high specific weight and low power density. Two-stroke engines have the advantage of high power, lightweight and low friction while premixed two-strokes have the major disadvantages of high fuel consumption and emissions from fuel short-circuiting. When combining the diesel cycle with two-stroke cycle, the problematic fuel shortcircuiting is eliminated through direct fuel injection while the low power density of diesel cycle is improved. In this research, the performance in terms of power output and fuel consumption of a 118cc two-stroke direct injection diesel engine was evaluated. Dynamometer testing and simulation of a prototype engine were conducted for that purpose. The prototype engine was built by converting an existing two-stroke gasoline engine while simulation was done using a one dimensional engine modeling software. The influence of injection timing, exhaust system tuning, compression ratio and combustion chamber geometry on engine performance was investigated. Experimental results show that the engine is capable of propelling a small motorcycle to a cruising speed of 60km/h with fuel consumption of 65km/l, while the ideal performance of the engine which was simulated by the engine model gives maximum cruising speed of 70km/h with mileage of 77km/l.